Injectable Collagen Implant Improves Survival, Cardiac Remodeling, and Function in the Early Period After Myocarditis in Rats. (September 2014) - Rinkevich-Shop, Shunit; Landa-Rouben, Natalie; Epstein, Frederick H.; Holbova, Radka; Feinberg, Micha S.; Goitein, Orly; Kushnir, Tammar; Konen, Eli; Leor, Jonathan
Aim: Despite clear evidence of immune system involvement in the pathogenesis of myocarditis, the treatment of myocarditis remains nonspecific and supportive. We sought to test the hypothesis that injection of a collagen-based implant into the inflamed myocardium would stabilize the left ventricular (LV) wall and prevent adverse remodeling and dysfunction. Methods and Results: Autoimmune myocarditis was induced in 42 male Lewis rats. Development of myocarditis was evaluated and confirmed by serial echocardiography and cardiac magnetic resonance scans, LV wall thickening, global and regional LV wall motion abnormalities, and in some cases pericardial effusion. Sick animals were randomized to either injectable collagen implantation or saline injection into the anterior inflamed myocardium 14 days after immunization. Significantly, injectable collagen implantation improved 31-day survival compared with controls (85.7% vs 50%; P = .03). Furthermore, although injectable collagen significantly attenuated LV systolic and diastolic dilatation and preserved LV geometry and function, control animals developed significant LV dilatation and dysfunction. These favorable effects on LV remodeling were confirmed by postmortem morphometry. Significantly, the injectable collagen implant attenuated cardiomyocyte hypertrophy and infiltration of macrophages and lymphocytes into the myocardium. Conclusions: The present study shows, for the first time, that injectable collagen biomaterial improves survival and attenuates cardiac inflammation, cardiomyocyte hypertrophy, LV remodeling, and dysfunction in the early period after myocarditis in rats. Our findings suggest a new biomaterial-based strategy to ameliorate the devastating effects of myocarditis.